Autoregulation of cerebral blood flow during controlled hypotension in baboons. Issue 10 (October 1976) - Fitch, W.; Ferguson, G. G.; Sengupta, D.; Garibi, J.; Harper, A. Murray
Abstract : The effect of graded, progressive hypotension on the autoregulation of cerebral blood flow was studied in anaesthetised baboons. Progressive hypotension was produced over a period of four to five hours, either by graded haemorrhage or by the administration of increasing concentrations of hypotensive drugs. During haemorrhagic hypotension autoregulation was maintained until the mean arterial pressure had decreased to 65% of its baseline value, below which cerebral blood flow was pressure passive. In those animals subjected to drug-induced hypotension, autoregulation persisted to lower levels of mean arterial pressure (35-40% of baseline). It is postulated that under conditions of haemorrhagic hypotension, constriction of the extraparenchymal cerebral vessels in response to sympathetic stimulation decreases the possible range of autoregulation in the anaesthetised baboon.